EFFECT OF SUBSTITUSION OF BREAD WASTE ON COMERSIAL RATIONS ON INTERNAL FAT DISTRIBUTION OF SUPERIOR BALITNAK (KUB) CHICKENS - A., Miskadi; Ariana, I N. T.; Ardika, I N. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the effect of substitusion of bread waste on comersial rations on internal fat distribution of superior balitnak (KUB) chickens. This research was conducted from July to September 2021 on a farm Mr. Gede Suarta farm, The farm Location is in Banjar Tengah Gulingan Street, Gulingan, Mengwi, Badung, for 8 weeks. The research design is use a completely randomized design (CRD) which consist of 3 treatments and 5 replications. Each replication consist of 2 KUB chickens aged 1 week with homogeneous of body weight. The treatments are P0 : 100% commercial ration CP 511; P1: 75% commercial ration CP 511 + 25% bread waste; and P2: 50% commercial ration CP 511 + 50% bread waste. The variables observed were: Pad fat, mecenteric fat, ventriculus fat, and abdominal fat. The results showed that the average percentage of fat weight of KUB chicken pads on the provision of 25% and 50% bread waste was significantly different (P<0.05), the percentage of mesenteric fat weight of P1 and P2 statistically showed no significant difference (P>0.05), the average percentage of KUB chicken ventriculus fat weight in treatments P1 and P2 statistically showed no significant difference (P>0.05), and the average percentage of KUB chicken abdominal fat in treatments P1 and P2 statistically showed a significant difference (P<0, 05) compared to treatment P0. The conclusion of this study was that the replacement of commercial rations with bread waste as much as 25% and 50% had no effect on the percentage of intestinal fat (mesentric fat) and bile fat (ventriculus fat), but had an effect on increasing the percentage of pad fat (pad fat) and the percentage of abdominal fat. (abdominal fat). Keyword : Kub chickens, internal fat, bread waste, commercial ration.